Lignin-Derived Activated Carbon as Electrode Material for High-Performance Supercapacitor - Chenghao Pan; Yongfeng Ji; Suxia Ren; Tingzhou Lei; Lili Dong (Molecules)
Utilizing lignin-derived activated carbon in supercapacitors has emerged as a promising approach to alleviating environmental pollution and promoting the high-value utilization of byproducts in the papermaking industry. In this study, activated carbons (LACs) were prepared using a simple one-step KOH activation approach and by employing enzymatic hydrolysis lignin (EHL). The impact of the KOH activation parameters on the microstructure and capacitive performance of the LACs was investigated by varying the KOH/EHL ratio and activation temperature. The optimized sample LAC800-4 showed an interconnected porous structure with a high surface area of 2285 m2/g, abundant micropores, and a small number of mesopores, which makes it a suitable electrode material for supercapacitors. The sample LAC800-4 demonstrated a high specific capacitance of 291.3 F/g in a three-electrode system. Under a symmetrical supercapacitor electrode system, the specific capacitance of the LAC800-4 electrode reached 186.8 F/g at 0.5 A/g. After 10,000 cycles at 20 A/g, the capacitance retention rate remained at 96.1%. The symmetrical supercapacitor also demonstrated a superior energy density of 6.5 Wh/kg. This work provides valuable insights into the transformation of low-value natural biomass derivatives into environmentally friendly, high-performing supercapacitor electrode materials.